Fully Endoscopic Retrosigmoid Vestibular Nerve Section for Refractory Meniere Disease - Setty, Pradeep; Babu, Seilesh; LaRouere, Michael J.; Pieper, Daniel R. (Journal of Neurological Surgery Part B: Skull Base, 2016)
Objective This study aims to report our results and technical details of fully endoscopic retrosigmoid vestibular nerve section.Design A prospective observational study was conducted.Setting A single academic, tertiary institution involving neurosurgery and neurotology.Participants Previously diagnosed patients with Meniere disease, refractory to medical therapy, who underwent fully endoscopic vestibular nerve section.Main Outcome Measures Postoperative improvement in vertiginous symptoms as well as hearing preservation, based on the American Association of Otolaryngology-Head and Neck Surgeons score and the Gardener and Robertson-Modified Hearing Classification. Facial nerve preservation based on the House–Brackman (HB) score.Results Symptoms improved or resolved in 38 of 41 (92.2%) patients with only 1 of 41 (2.4%) reporting worsening symptoms. All 41 patients (100%) had a postoperative HB score of 1/6, demonstrating full facial nerve preservation. Hearing was stable or improved in 34 of 41 (82.9%) patients. Three complications took place for a rate of 7.3%, one cerebrospinal fluid leak, and two wound infections. Conclusion The fully endoscopic approach to vestibular nerve sections is a safe and effective technique for the treatment of medically refractory Meniere disease. This technique also utilizes smaller incisions, minimal cranial openings, and no cerebellar retraction with improved visualization of the cerebellopontine angle neurovascular structures.
Keywords: cerebellopontine angle; endoscopy; Meniere disease; skull base